2019
DOI: 10.1111/bju.14841
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term incidence of secondary bladder and rectal cancer in patients treated with brachytherapy for localized prostate cancer: a large‐scale population‐based analysis

Abstract: ConclusionsBrachytherapy predominantly increases the risk of secondary BCa and, to a lesser extent, that of RCa. Follow-up of such patients is therefore required. It is encouraging that both secondary BCa, and RCa rates, in particular, have recently decreased, RCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The risk of SPM could be increased by interactions between common etiological factors, particularly an unhealthy lifestyle (e.g., long-term tobacco use, excessive intake of alcohol), genetic susceptibility, environmental exposure, and patient factors (7,9). In addition, research has shown that SPM can develop as a result of the late effects of certain treatments [e.g., radiotherapy, chemotherapy (10,11)].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of SPM could be increased by interactions between common etiological factors, particularly an unhealthy lifestyle (e.g., long-term tobacco use, excessive intake of alcohol), genetic susceptibility, environmental exposure, and patient factors (7,9). In addition, research has shown that SPM can develop as a result of the late effects of certain treatments [e.g., radiotherapy, chemotherapy (10,11)].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that the main hematological cancers, Kaposi sarcomas and gastrointestinal tract (GIT) tumors were cancers with the risk of occurring before (BL/L as an SPC) or after (any cancer other than BL/L as an SPC) BL/L. Other population-based studies also using the SEER Program reported the occurrence of further malignancies after a previous cancer including prostate [ 28 ], breast [ 29 ] and chronic myeloid leukemia [ 30 ].…”
Section: Discussionmentioning
confidence: 95%
“…Curative treatment of prostate cancer mainly consists of prostatectomy with or without RT and/or ADT according to the estimated risk of recurrence [ 9 ]. Patients with prostate cancer who receive RT are at higher risk of secondary malignancies, such as bladder and rectal cancers [ 10 12 ]. In our case, rectal cancer was found 1.5 years after diagnosis of prostate cancer, which was treated with RT, therefore, it is likely that the rectal cancer was caused by RT for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%